2021
DOI: 10.1177/14651165211051171
|View full text |Cite
|
Sign up to set email alerts
|

Learning about the unknown Spitzenkandidaten: The role of media exposure during the 2019 European Parliament elections

Abstract: The Spitzenkandidaten were meant to personalize European Parliament elections. This paper asks whether and through which channels the lead candidates were actually able to make themselves known among voters – a necessary precondition for any electoral effect. Combining panel surveys and online tracking data, the study explores candidate learning during the German 2019 European Parliament election campaign and relates learning to different types of news exposure, with a special focus on online news. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Following Cronin et al (2022), we divide this raw count by the number of active days before each wave, i.e., days on which the individual registered any online activity. Finally, we follow Richter and Stier (2022) in adding +1 and then log-transforming this raw count to account for extreme outliers and likely diminishing returns. For example, an extra 10 alternative news articles likely have a higher impact on an individual who almost never consumes alternative news compared to individuals for whom the count of articles is already in the hundreds.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Cronin et al (2022), we divide this raw count by the number of active days before each wave, i.e., days on which the individual registered any online activity. Finally, we follow Richter and Stier (2022) in adding +1 and then log-transforming this raw count to account for extreme outliers and likely diminishing returns. For example, an extra 10 alternative news articles likely have a higher impact on an individual who almost never consumes alternative news compared to individuals for whom the count of articles is already in the hundreds.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Still, the vast majority of results from the main models are replicated, though the dummy within-effect on environmental protection is erased whilst the count between-effect on affective polarization is again statistically significant in the negative direction (Figure A6). Second, we operationalise extent of consumption both as simply the log of the raw count (Richter and Stier, 2022) and the raw count divided by the active days (Cronin et al, 2022), essentially decomposing the main operationalisation into the two transformations we applied to the raw count. The logged count model (Figure A7) returns a statistically significant and negative between-effect on affective polarization, the only outcome for which we find repeated evidence (across robustness checks) that the extent of consumption matters.…”
Section: Robustness Checksmentioning
confidence: 99%
“…Considering the importance of news in the context of electoral campaigns for information-gathering processes of voters outlined by Richter and Stier (2022), this framing analysis focuses on traditional Colombian newspapers chosen for their accessibility from outside the country through the help of data archives. The Nexis Uni online newspaper archive was mainly used for data collection.…”
Section: B Datamentioning
confidence: 99%
“…[…] Si su triunfo se concretara, Colombia jamás volvería ser la misma y nuestra democracia estaría en grave riesgo. [30,Annex I] By assuming that "any way of fighting" would be viable for Petro, his past is associated with his current political career, implying that he would potentially use illegitimate means to achieve his electoral goals. Thus, his potential win would put Colombia and its democracy at high risk.…”
Section: B El Nuevo Siglomentioning
confidence: 99%
“…For instance, Hobolt (2014) showed that awareness of the Spitzenkandidaten existence and of specific lead candidates was minimal in most Member States, while also stressing that "presidential candidates did not play a major role in the election campaigns, except in a handful of countries, and thus had a limited impact on voter participation and vote choices" (p. 1528; on this matter, see also Schulze 2016). National parties gave little salience to the Spitzenkandidaten process (Braun and Popa 2018), and while media consumption slightly increases the odds of being able to express a preference for a lead candidate, it has become increasingly unlikely for the average citizen to find information about the lead candidates in the media (Gattermann et al 2016;Gattermann 2020;Richter and Stier 2022;Fotopoulos and Morganti 2022). Levels of engagements achieved by the lead candidates on Twitter were also remarkably low (e.g., Rivas-de-Roca and García-Gordillo 2020).…”
Section: Introductionmentioning
confidence: 99%